2010
DOI: 10.1128/jcm.02518-09
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Alpacas ( Lama pacos ) Caused by Mycobacterium bovis

Abstract: We report three cases of tuberculosis in alpacas from Spain caused by Mycobacterium bovis. The animals revealed two different lesional patterns. Mycobacterial culture and PCR assay yielded positive results for M. bovis. Molecular typing of the isolates identified spoligotype SB0295 and identical variable-number tandem repeat (VNTR) allele sizes. CASE REPORT Herd 1. The affected herd comprised 32 alpacas (26 adults and six juveniles) and was located in the Ronda region (southern Spain). The animals were raised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 20 publications
2
22
0
3
Order By: Relevance
“…In pulmonary form, giant cells and AFB were either absent or occasionally observed, whereas they were seen frequently in disseminated form. Similar lesions have been previously reported in M. bovis infection in camels (García-Bocanegra et al 2010;Mamo et al 2011). Similar to the findings of the present study, the respiratory tract was observed as the main target in camels infected with M. bovis (Mamo et al 2011) which suggests that respiratory route could be the main route of infection in camels.…”
Section: Discussionsupporting
confidence: 92%
“…In pulmonary form, giant cells and AFB were either absent or occasionally observed, whereas they were seen frequently in disseminated form. Similar lesions have been previously reported in M. bovis infection in camels (García-Bocanegra et al 2010;Mamo et al 2011). Similar to the findings of the present study, the respiratory tract was observed as the main target in camels infected with M. bovis (Mamo et al 2011) which suggests that respiratory route could be the main route of infection in camels.…”
Section: Discussionsupporting
confidence: 92%
“…More recently, there has been a move towards more conservative surgical management in humans because M. ulcerans has a relatively predictable antibiogram. avium, 34 M. bovis, 35 M. microti 36,37 and M. kansasii; 38,39 however, no reports of treatment of these infections (from which treatment of M. ulcerans infection could be extrapolated) have been recorded. 33 A recent case series of dogs with M. ulcerans infection confirmed that the combination of rifampicin and a fluoroquinolone (with or without surgical debridement) was effective in curing the disease within 8-10 weeks in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…S1 in the supplemental material). Spoligotyping (17) revealed an identical spoligotype profile, SB0295, for the three alpaca isolates (11). We excluded the possibility of infection in the country of origin in the case of the United Kingdom, because this spoligotype has not been reported (5,14), and we ignore the situation in Peru due to the lack of molecular typing data from this country.…”
mentioning
confidence: 99%
“…Molecular typing methods such as spoligotyping (17) and multilocus variable number tandem repeat (VNTR) analysis (10,29) are wildly used to clarify epidemiological relations between outbreaks. Recently, three cases of M. bovis in alpacas (Lama pacos) have been reported as the first description of tuberculosis in this animal species in Spain (11). Since trade with camelids is increasing and scarce legislation addressing tuberculosis in these animals is given, a follow-up by molecular typing was deemed advisable to obtain insight into its epidemiology.…”
mentioning
confidence: 99%